Revision of the hillstream lizard loaches, genus Balitoropsis (Cypriniformes: Balitoridae) - Randall, Zachary S.; Riggs, Patrick A. (Zootaxa, 2015)
The genus Balitoropsis Smith 1945 consists of two species, B. zollingeri (Bleeker 1853) and B. ophiolepis (Bleeker 1853). Homaloptera maxinae Fowler 1937, Balitoropsis bartschi Smith 1945, and Homaloptera nigra Alfred 1969 are junior synonyms of B. zollingeri. Balitoropsis zollingeri has been reported from Thailand, Laos, Cambodia, Malay Peninsula, Sumatra, Java, and Borneo, and B. ophiolepis is known from Sumatra, Java, and Borneo.